Low Tortuosity 3D‐Printed Structures Enhance Reaction Kinetics in Electrochemical Energy Storage and Electrocatalysis. Issue 12 (27th September 2022) - Xue, Xinzhe; Lin, Dun; Li, Yat
Abstract : Additive manufacturing offers new and exciting opportunities for the digital fabrication of energy storage and electrocatalytic devices. Herein, the important role of 3D‐printed low‐tortuosity structures in improving thick electrodes' electrochemical kinetics (mass transfer and charge transfer) is highlighted. First, the key factors determining the electrochemical kinetics in open porous structures and the commonly used computational and experimental characterization methods for porous structures are reviewed. Then, various 3D‐printed energy storage and electrocatalytic electrodes and devices, focusing on the contribution of low‐tortuosity structure to electrochemical kinetics are featured. Finally, thoughts about the prospects and challenges of 3D‐printed energy storage and electrocatalytic systems are shared. Abstract : Additive manufacturing offers new and exciting opportunities for fabricating structures with high structural complexity. This article highlights the critical role of low‐tortuosity structures in improving thick electrodes' electrochemical kinetics (mass transfer and charge transfer) and reviews the implementation of these electrodes for energy storage and electrocatalysis devices. This review also provides perspectives on the future research development of 3D‐printed electrodes.